Visit-to-Visit Office Blood Pressure Variability and Cardiovascular Outcomes in SPRINT (Systolic Blood Pressure Intervention Trial). Issue 4 (October 2017) - Chang, Tara I.; Reboussin, David M.; Chertow, Glenn M.; Cheung, Alfred K.; Cushman, William C.; Kostis, William J.; Parati, Gianfranco; Raj, Dominic; Riessen, Erik; Shapiro, Brian; Stergiou, George S.; Townsend, Raymond R.; et al.
Abstract : Studies of visit-to-visit office blood pressure (BP) variability (OBPV) as a predictor of cardiovascular events and death in high-risk patients treated to lower BP targets are lacking. We conducted a post hoc analysis of SPRINT (Systolic Blood Pressure Intervention Trial), a well-characterized cohort of participants randomized to intensive (<120 mm Hg) or standard (<140 mm Hg) systolic BP targets. We defined OBPV as the coefficient of variation of the systolic BP using measurements taken during the 3-, 6-, 9-, and 12-month study visits. In our cohort of 7879 participants, older age, female sex, black race, current smoking, chronic kidney disease, and coronary disease were independent determinants of higher OBPV. Use of thiazide-type diuretics or dihydropyridine calcium channel blockers was associated with lower OBPV whereas angiotensin-converting enzyme inhibitors or angiotensin receptor blocker use was associated with higher OBPV. There was no difference in OBPV in participants randomized to standard or intensive treatment groups. We found that OBPV had no significant associations with the composite end point of fatal and nonfatal cardiovascular events (n=324 primary end points; adjusted hazard ratio, 1.20; 95% confidence interval, 0.85–1.69, highest versus lowest quintile) nor with heart failure or stroke. The highest quintile of OBPV (versus lowest) was associated with all-cause mortality (adjusted hazard ratio, 1.92; confidence interval, 1.22–3.03) although the association of OBPV overall with all-cause mortality was marginal ( P =0.07). Our results suggest that clinicians should continue to focus on office BP control rather than on OBPV unless definitive benefits of reducing OBPV are shown in prospective trials. Clinical Trial Registration—: URL:http://www.clinicaltrials.gov . Unique identifier: NCT01206062 Abstract : Supplemental Digital Content is available in the text.